Answer :

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c


For the given equation


=


And either of their sum or difference = b


=


Thus the two terms are (a + 4) & (a-2)


Difference = (a + 4)-(a-2)


= 6


Product = (a + 4)(a-2)


=






x[x + (a + 4)]-(a-2)[x + (a + 4)] = 0


[x-(a-2)][x + (a + 4)] = 0


[x-(a-2)] = 0 or [x + (a + 4)] = 0


x = (a-2) or x = -(a + 4)


Hence roots of equation are x = (a-2) or-(a + 4)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses